PENGARUH TINGKAT PENDIDIKAN, KETERAMPILAN KERJADAN SIKAP KERJA TERHADAP PRESTASI KERJA KARYAWAN DI SEKOLAH TINGGI MANAJEMEN IMMI JAKARTA - Dewi Listiorini (Sekolah Tinggi Manajemen IMMI Jakarta, 2022)
The purpose of this study was made to determine how the effect of educational level on employee performance, jobskills to the job performance, work attitude on job performance and to know how to influence the level of education,job skills and work attitudes on work performance in the School of Management Study IMMI.By using a sample of 35 people using questionnaires. Data were tested by used validity test, realibity test,normality test and classic assumption test.Analysis of data using multiple linear regression. T test and f test. The results of this study are education level gavesignificant positive effect on job performance, job skills gave significant positive effect on job performance, workattitude gives significant positive effect on work performance and level of education and job skills also work attitudessignificant positive effect on job performance.